OVERVIEW OF THE EPIDEMIC SITUATION ON CERTAIN INFECTIOUS ANIMAL DISEASES IN THE RUSSIAN FEDERATION IN 2018 - N. S. Bardina; A. V. Varkentin; A. K. Karaulov (Ветеринария сегодня)
The paper presents the results of analysis of epidemic situation on infectious animal diseases subject to compulsory OIE notification: FMD, African swine fever, classical swine fever, lumpy skin disease, sheep and goat pox, and highly pathogenic avian influenza. The paper presents data on the specified diseases situation in the Russian Federation, broken down by Subjects, and also provides a comparative description of the data for 2017 and 2018. Besides, attention is focused on some features of the epidemic process, depending on the season. For a long time the Russian Federation has been infected with several highly dangerous animal diseases, such as African and classical swine fever, FMD, lumpy skin disease, sheep and goat pox, and highly dangerous avian influenza. The specified above infections cause great damage to animal husbandry in the country which has a negative impact on its export potential. Analysis of the ASF epidemic situation demonstrates that the Russian Federation has been permanently infected and there is a trend for the geographic spread of the epidemic. Despite the fact that the number of ASF outbreaks newly detected in 2018 is almost half that of 2017, the situation remains tense. The forecast is still unfavorable. Lumpy skin disease has been reported in the Russian Federation for four years already. Herewith, from year to year the disease has been invading new territories. The HPAI epidemic situation is of great concern as in 2018 82 outbreaks were reported in poultry population which is 2.3 times more than in 2017. Besides, there is a trend for the epidemic extension. Thus, in 2018 avian influenza was reported in previously disease free Subjects of the Russian Federation. In 2018 the Russian Federation remained permanently infected with FMD, sheep and goat pox, and classical swine fever.